THE INFLUENCE OF PROFITABILITY, INSTITUTIONAL OWNERSHIP, AND MANAGERIAL OWNERSHIP ON STOCK RETURN IN THE ENERGY SECTOR - Aurora, Jessica Verlyn; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2025)
This study aims to examine how stock returns in the energy sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 timeframe are impacted by profitability, institutional ownership, and management ownership. With the aid of Microsoft Excel 2016 and SPSS version 25, multiple linear regression analysis was performed on secondary data taken from firm financial reports. The percentage of shares held by institutions is the basis for institutional ownership, the percentage of shares held by firm management is the basis for managerial ownership, and Return on Assets (ROA) is the basis for profitability. The findings demonstrate that profitability positively and significantly impacts stock returns, suggesting that more profitable businesses typically offer larger stock returns. The fact that managerial and institutional ownership have no discernible impact on stock returns, however, suggests that managerial shareholding and institutional investor participation have no direct bearing on a company's stock performance. This analysis suggests that while institutional and management ownership are not determining variables in predicting stock returns, investors should prioritize profitability when making judgments about energy sector investments.